Learning from the Past: A Fifty-year Perspective on Pakistan’s Development (Distinguishedl Lecture) (The Pakistan Development Review, 1997)
In some ways, Pakistan’s economic growth since 1947 has been remarkable. The country’s economic viability was considered, in some quarters,1 in serious doubt at its emergence, but it has managed, despite a quadrupling of the population, to bring about significant improvement in the average living standards. Per capita GNP growth, on average around 2 percent per annum over a long stretch of nearly fifty years, has been the best among countries of the subcontinent. This growth has meant an increase in average income of about 150 percent over 1950–96. But Pakistan, like many other developing countries, has not been able to narrow the gap between itself and rich industrial nations which have grown faster on a per head basis. Also, Pakistan has lost substantial economic ground to the rapidly growing economies of East Asia notably China, South Korea, Thailand, Malaysia and Indonesia. In 1960, South Korea’s per capita income was only marginally ahead of Pakistan’s. In the short period of one generation, Korea had an income level which on purchasing power parity basis five times that of Pakistan in 1995. On the same basis, Thailand and Malaysia enjoyed a per capita income advantage of 200 to 300 percent over Pakistan (Table 2).